(untitled) (Prithvi Academic Journal, 2022)
Health and physical education helps a person to promote health status and prevent him or her from diseases in life. National Education System Plan (2071) recommended health and physical education as an obligatory subject in the schools’ curriculum, but at present it is an optional subject at the secondary level. In this context, this study aims to explore the students’ perception towards motivational and de-motivational factors of health and physical education for teacher education. To accomplish the objectives of the study, phenomenological research design under qualitative inquiry was applied. The data were collected through unstructured interview with the B.Ed. students of the constituent campuses under the public university. The informants were selected purposively. Decreasing of students in health and physical education for teacher education was the problem of this study. The results showed that the main motivational and de-motivational factors regarding health and physical education are: existing curriculum, teachers’ competencies, pedagogies applied in teaching-learning activities, availability of infrastructure facilities, employability after completion of the study, public recognition and evaluation practices. This implies that students, teachers and policymakers should work together to reform the subject’s sustainability and recognition.